Web-Based Production Engineering Inventory System At TVRi Bengkulu - Kodia, Elsi; Khairil, Khairil; Sari, Venny Novita (Utami Publisher, 2025)
Inventory system in a company is closely related to the activity of collecting data about activities and transactions in and out of a company's goods. Because inventory is so important to the company, the existence of an inventory system based on Information Technology (IT) is needed to facilitate recording and processing transactions compared to the manual method. Based on the results of discussion and testing, the following conclusions can be drawn, Web-based Production Techniques Inventory System at TVRI Bengkulu, can be used by the user to help find item data, borrower data, loan data, and return data using the Rapid Application Development method. Application development is carried out by applying the Rapid Application Development (RAD) method, because this method has advantages over other traditional methods in SDLC, namely the development cycle which only requires a relatively faster and shorter time. The process of developing this system is carried out systematically which has 3 stages, namely requirement planning, workshop design, implementation.